The Cascade of Global Norms: An Integral and Mimetic Analysis of National and Civil Society Leadership and Partnership in the Mine Ban Treaty - Lemieux, Sylvie (Université Saint-Paul / Saint Paul University, 2018)
Purpose – This research sets out to examine the roles of leadership and partnership in the successful cascade of a new global norm in the field of security. Theories on the norm lifecycle and mimetism are brought together with the integral approach (IA) in order to create a tool with which to map the relationships and processes of the norm cascade process. The Mine Ban Treaty (MBT) is the selected case study for both personal interests and for the simplicity of its process and its continuing success, 20 years after its endorsement by 122 nations in December 1997. The process was led by Canada. Four specific events during the 14-month period of the Ottawa Process are selected for analysis. The mapping tool allows for the understanding of both the individual and collective factors that validate a complex global cascade process. The selection of respondents—all of them Canadian members of the government–civil society coalition—affords some stimulating conclusions regarding leadership and partnerships, particularly in the form of exemplars, connectors, and co-leaders, necessary to the fostering of a successful normative change. Design/methodology/approach – The method employed consisted of a qualitative analysis of primary material, consisting of official documents on the one hand, and interviews with some of the major actors on the other, as well as related secondary literature. A constructivist analysis of the four IA quadrants was performed, with a particular focus on mimetic aspects, with a view to identifying the key indicators around which to build a questionnaire and platform for analysis. This exploratory phase resulted in the identification of two complex dynamics of transformation leading to leadership and partnership in the cascade phase. The chosen approach unveiled the layering and collaborative interconnectivities of the norm leader and norm partnerships. This led to a more profound understanding of the complexity of the cascade phase, which improves the possibility of transposing it to other normative change and conflict resolution scenarios. Findings – The two-part hypothesis was validated. The first part relates to how the mapping of the norm leader’s role allows for a richer understanding of the complexity of the cascading of global norms. The second part relates to how the combination of the integral approach and mimetism theory has enabled the capture of the leadership and partnership qualities that lead to a successful cascade process. The qualities reside in three elements: 1) the role of the exemplars, 2) the role of the connectors, and 3) trust as demonstrated through co-leadership. Originality/value – The originality of this dissertation lies in its amalgamation of the two theories of integral approach and mimetics to build an understanding of the cascading cycle of a global norm. Together these theories provide an expanded framework through which to understand the information surrounding the MBT. The deconstruction of the relations and processes leading to the successful execution of the cascade of the MBT allows for the identification of the dynamics of norm cascade, useful in any field of negotiations, such as at the national, provincial, municipal, or even organizational level.
Keywords: Global norm; normative change; integral approach; mimetic theory; leadership; partnership; government; civil society; cascade of norms; mine ban treaty; and conflict resolution.